Financial Accountability of Non-Profit Organizations under PSAK No. 45: A Case Study of Masjid Raya Taqwa Muhammadiyah, Medan - Putri Gami, Emelia Rahmadany; Harahap, Nur’ain; Marpaung, Ade Putra; Siregar, Hot Berlian; Susanto, Agus (Devitara Innovations, 2025)
This study aims to analyze the financial management accountability of a non-profit organization, particularly Masjid Raya Taqwa Muhammadiyah in Medan, based on the standards outlined in PSAK No. 45. As a non-profit entity, a mosque is obligated to prepare financial statements that are transparent and accountable to maintain public trust, especially from donors. However, the financial reporting practices observed at the mosque remain relatively simple and do not yet comply with PSAK No. 45, which includes the statement of financial position, statement of activities, statement of cash flows, and notes to the financial statements. This research employs a qualitative method with a case study approach. Data were collected through direct observation, interviews with mosque administrators, and documentation of financial records. The study found that the mosque management has shown an effort toward transparency by publicly announcing financial updates to the congregation on a weekly basis. Despite this, financial management practices still fall short of fulfilling both vertical and horizontal accountability as prescribed by PSAK No. 45. The results indicate a need for improved understanding and implementation of non-profit financial reporting standards. Enhancing the capacity of mosque administrators in applying PSAK No. 45 is essential to ensure more systematic, informative, and accountable financial reporting.